Energy Subsidies Reform in Jordan : Welfare Implications of Different Scenarios - Aziz, Atamanov; Jellema, Jon; Serajuddin, Umar (World Bank, Washington, DC, 2015)
As the Arab Spring unfolded and political unrest spread across the Arab world, Jordan faced an adverse economy as well. Fundamental to the economic challenge was high and rising energy prices, already heavily subsidized for consumers. With the government intent on staving off emerging political unrest through a series of measures, buffering consumers from increased energy prices being a key action, fiscal costs mounted. By 2012, subsidies on petroleum products alone were about 2.8 percent of GDP and 8.8 percent of government expenditures. At the same time, political unrest disrupted the supply of natural gas from Egypt and Jordan abruptly had to switch to using imported oil products (heavy fuel oil and diesel) to produce electricity. Consequently, the cost of producing electricity increased several folds. As the increased cost was not passed on to the consumers, National Electric Power company (NEPCO), bore all the increases in fuel prices and accumulate debt as a result. At approximately 17 percent of government expenditures and 5.5 percent of GDP in 2011, this was twice the amount of the petroleum subsidies. The chapter is organized as follows. Section two traces the evolution of subsidies in Jordan in recent times. The distributional impacts of reform would depend on how important the subsidized items are to consumers in terms of their expenditures on those items. Section three discusses this question from the perspective of richer and poorer households. The distributional impacts of reform would of course not only depend on how much consumers spend on the subsidized items but also on the extent of price changes. Sections four and five simulate direct and indirect impacts of potential reform scenarios across the income distribution. From this discussion, in section six the chapter moves onto considering how reforms are weighed down by vexing political economy constraints. In MENA countries, universal subsidies have been in place as part of the government’s role in ensuring stability in the lives of the people and doing away with them is not straightforward.